Development of an Electrochemical Biosensor Using Magnetite Nanoparticles - Panakamon Thonglor; Somchai Sonsupup; Tanayt Sinprachim; Naphat Albutt (Key engineering materials, 2024)
An electrochemical sensor was enhanced with magnetite nanoparticles for biosensor application. Nanoparticles of magnetite (Fe 3 O 4 ) ranging in size from 5 to 30 nm were produced by the co-precipitation method and further modified with an amine functional group (Fe 3 O 4 @SiO 2 _NH 2 ). During the process, the functional amine served as a supporting biomaterial and coating agent, regulating particle size and aggregation. The Fe 3 O 4 @SiO 2 _NH 2 nanoparticles were incorporated into gold nanoparticle planes on a conductive graphene electrode in a diluted solution of the ultrafast redox probe K 3 [Fe(CN) 6 ]. Using scanning electron microscopy to investigate the morphology of the modified graphene sheets and gold (Au) nanoparticles on screen printed electrodes (SCPE). The results clearly demonstrated the even distribution of Fe 3 O 4 nanoparticles, almost always less than 30 nm in size, on AuNPs and graphene sheets. Adding these magnetite particles has created active sites, facilitating the movement of electrons from redox-active species in the solution. In addition, the electrochemical reduction of flawed graphene sheets has greatly limited the oxygen groups, making the material more conductive or enhancing signal. The sensor was subsequently investigated with the use of magnetite nanocomposites for electrochemical biosensing applications with (bovine serum albumin) BSA.
Keywords: Advanced biosensing and bioanalysis techniques; Electrochemical sensors and biosensors; Electrochemical Analysis and Applications